Inhalation of multiple pen caps causing bronchial foreign bodies: a rare case in an older child - Jia Zhai; Yongsheng Guo; Chunlei Chen; Xuelin Wang; Yifan Wang; Ying-Xue Zou (BMC Pediatrics)
Abstract Background Foreign body inhalation is rare in older children, often leading to underdiagnosis and delayed treatment. Most cases involve a single foreign body, but instances of multiple foreign bodies are exceedingly uncommon. This report presents a case of an elder child who inhaled two pen caps, emphasizing the need for clinical vigilance and thorough medical history collection. Case presentation A twelve-year-old boy was admitted with a persistent cough lasting over two months, accompanied by sputum with a peculiar odor. Previous treatments with oral Cefdinir (0.1 g, three times daily) and inhaled Budesonide Suspension had not improved his condition. Physical examination revealed decreased breath sounds on the right side without signs of respiratory distress or wheezing. Imaging studies, including chest X-ray and CT scan, along with bronchoscopy, confirmed the presence of two foreign bodies in the right bronchus. The patient was started on anti-infective therapy to address any underlying infection before proceeding with removal. A combination of flexible bronchoscopy and rigid bronchoscopy, supplemented by a cryotherapy instrument, successfully extracted the pen caps. Post-procedure assessments indicated that the patient’s body temperature returned to normal, cough symptoms resolved, and lung ventilation significantly improved. Conclusion This case highlights the critical need for clinicians to remain vigilant regarding bronchial foreign bodies in older children. The rare occurrence of multiple foreign bodies, particularly resulting from active inhalation, necessitates a comprehensive medical history during patient evaluation. Early recognition and intervention can lead to significant improvements in patient outcomes, underscoring the importance of thorough clinical assessment in similar cases.